Analysis of reinforced concrete tilt-up panels utilizing high-strength reinforcing bars - McConnell, Sam (Kansas State University, 2017)
Recent years have witnessed the advent of many innovative materials to the construction industry. These materials often offer benefits to the projects on which they are used, but only if they are utilized in the proper applications. Among these new materials is high-strength reinforcing steel for use in reinforced concrete structural elements. This material is not new from the perspective of chemical composition, but rather the applications that it is being selected for. The following paper details the evaluation of the use of high-strength steel reinforcement in the design of reinforced concrete tilt-up panels and compares those designs to that of standard strength reinforcement. For the purpose of this study, standard strength is defined as reinforcement having a tensile yield stress of 60ksi while high-strength reinforcement refers to reinforcing steel with a tensile yield stress of 80ksi. 120 panels are designed for both high-strength and standard strength reinforcement, and the resulting steel spacings are compared. This study provides data from which designers and contractors can improve their ability to provide quality tilt-up panel designs.
Keywords: Reinforcement; Rebar; High-strength; Slender wall; PanelTilt-up